Transfer of technologies: a cross-disciplinary taxonomy - Reisman, Arnold (Omega (Oxford), 2005)
Transfer of technologies (TT) takes place among various kinds of players, takes on various kinds of modalities and is done for various motivations. Its literature is very disjoint and disparate. It transcends several academic disciplines and professions. This paper presents a taxonomy defining the field in its entirety and delineating all of its facets in a manner that is parsimonious yet discriminating. Many potential uses for the taxonomy are identified. These include more effective teaching of TT subject matter.